Ideal guidance and procedures for donning and doffing personal protective equipment to be used by health workers during management of patients confirmed with COVID-19 or person under investigation - Ahmad, Saima; Manzoor, Haseeb; Chaudhary, Fatima Gul (International Journal Of Community Medicine And Public Health, 2020)
Highly infectious disease epidemics such as COVID-19 put healthcare workers at higher risk of infection than regular people as they come into more potential contact with contaminated respiratory droplets and so caution is warranted in the use of personal protective equipment (PPE) to lessen risk. It is not clear what kind of PPE best offers protection and the best way to remove PPE. PPE is used by Healthcare workers in the COVID-19 virus disease situation. Its use is an integral part of the strategy to combat COVID-19 and prevent its spread. Optimal PPE use is hard and thus healthcare workers may alter the delivery of care because of improper PPE use. Preventing contamination of PPE during donning and doffing therefore becomes crucial and requires improvisation. Donning and doffing of PPE should include adherence to protocols as well as COVID- 19 specific design of PPE and further research into the risks, benefits, and best practices of PPE use. Lastly, training of users must be stressed to minimize protocol deviations and in turn guarantee the best protection to HCWs. While ranked as the lowest in infection control hierarchy due to its effectiveness as compared to other measures and high cost, PPE is nonetheless extremely important and often overlooked aspect during early outbreak stages of a pandemic where neither drugs nor vaccines are available and access to them is limited. This paper sheds light on the donning and doffing protocols that should be used as well as discusses this often-overlooked aspect of the virus control measure.